Optimal least square vector autoregressive moving average for battery state of charge estimation and forecasting - Angela Caliwag (Elsevier, 2021)
The error in state of charge estimation using the combined models is usually attributable to the statistical model. In this study, a least square algorithm is utilized to optimize and increase the state of charge estimation accuracy. Specifically, the vector autoregressive moving average statistical model is optimized using the least square algorithm. The results presented in this paper show that the proposed method is effective in eliminating the estimation and measurement noise using the conventional statistical method and in optimizing the SoC estimation and forecasting. The optimization of the statistical model increases the SoC estimation and forecasting accuracy by 59.11%.